Blood oxidative stress markers and Plasmodium falciparum malaria in non‐immune African children. (February 2014) - Aguilar, Ruth; Marrocco, Tiziana; Skorokhod, Oleksii A.; Barbosa, Arnoldo; Nhabomba, Augusto; Manaca, Maria N.; Guinovart, Caterina; Quintó, Llorenç; Arese, Paolo; Alonso, Pedro L.; Dobaño, Carlota; Schwarzer, Evelin
Summary Converging in vitro evidence and clinical data indicate that oxidative stress may play important roles in Plasmodium falciparum malaria, notably in the pathogenesis of severe anaemia. However, oxidative modifications of the red blood cell (RBC)‐membrane by 4‐hydroxynonenal (4‐HNE) and haemoglobin‐binding, previously hypothesized to contribute mechanistically to the pathogenesis of clinical malaria, have not yet been tested for clinical significance. In 349 non‐immune Mozambican newborns recruited in a double‐blind placebo‐controlled chemoprophylaxis trial, oxidative markers including 4‐HNE‐conjugates and membrane‐bound haemoglobin were longitudinally assessed from 2·5 to 24 months of age, at first acute malaria episode and in convalescence. During acute malaria, 4‐HNE‐conjugates were shown to increase significantly in parasitized and non‐parasitized RBCs. In parallel, advanced oxidation protein products (AOPP) rose in plasma. 4‐HNE‐conjugates correlated with AOPP and established plasma but not with RBC oxidative markers. High individual levels of 4‐HNE‐conjugates were predictive for increased malaria incidence rates in children until 2 years of life and elevated 4‐HNE‐conjugates in convalescence accompanied sustained anaemia after a malaria episode, indicating 4‐HNE‐conjugates as a novel patho‐mechanistic factor in malaria. A second oxidative marker, haemoglobin binding to RBC‐membranes, hypothesized to induce clearing of RBCs from circulation, was predictive for lower malaria incidence rates. Further studies will show whether or not higher membrane‐haemoglobin values at the first malaria episode may provide protection against malaria.